Nitrogen-doped manganese-loaded layered double hydroxide as well as preparation and application thereof

By using nitrogen-doped manganese layered double hydroxide catalysts, the problems of high ozone oxygen consumption, large catalyst usage and high cost in the catalytic decomposition of methylmercaptan are solved, and the effective, low-cost and stable methylmercaptan waste gas treatment effect is achieved.

CN119746846AActive Publication Date: 2025-04-04TIANJIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411935461.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In the catalytic decomposition of existing catalysts, there are problems such as high ozone oxygen consumption, large catalyst usage, high cost and carbon deactivation in the catalytic decomposition of methylmercaptan, making it difficult to achieve efficient, low-cost and stable methylmercaptan waste gas treatment.

Method used

Nitrogen-doped manganese layered double hydroxide is used as a catalyst to prepare by ultrasonic mixing and calcining, and the layered structure and nitrogen and manganese dual active sites are used to achieve efficient catalytic decomposition of methanethiol.

Benefits of technology

The catalytic decomposition of methanethiol with high activity, low dosage and low energy consumption was achieved. The O3/CH3SH molar ratio was only 0.8 to achieve a conversion efficiency of 95%. After continuous use for 4 hours, the conversion efficiency remained above 90%, which significantly improved the stability and economicality of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746846A_ABST
    Figure CN119746846A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of methyl mercaptan waste gas treatment, in particular to a nitrogen-doped manganese-loaded layered double hydroxide as well as preparation and application thereof. The invention provides a preparation method of nitrogen-doped manganese-loaded layered double hydroxide, which comprises the following steps: ultrasonically mixing layered double hydroxide and manganese salt in water to obtain a mixed solution, then adding melamine and water into the mixed solution, ultrasonically mixing again to obtain a precursor, and calcining the precursor to obtain the nitrogen-doped manganese-loaded layered double hydroxide. The nitrogen-doped loaded manganese layered double hydroxide has nitrogen and manganese double active sites and has a good ozone catalytic oxidation treatment effect on methyl mercaptan.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of methyl mercaptan waste gas treatment, and in particular to a nitrogen-doped manganese-loaded layered double hydroxide and a preparation method and application thereof. Background Art

[0002] Methyl mercaptan (CH 3 Methyl mercaptan (SH) is a sulfur-containing volatile organic pollutant with a strong rotten cabbage smell, and its olfactory threshold is extremely low, only 0.0021ppm. Methyl mercaptan is widely present in environments such as the petroleum industry, sewage treatment plants and sanitary landfills, and its concentration ranges from tens to hundreds of ppm. High concentrations of methyl mercaptan are not only toxic to the human nervous system, but may also cause acid rain, equipment corrosion and catalyst deactivation in the chemical industry. With the continuous increase in my country's environmental protection efforts, strengthening the treatment and prevention of methyl mercaptan tail gas has become a top priority. Therefore, research and development of efficient methyl mercaptan waste gas / flue gas treatment technology has important practical significance.

[0003] At present, the removal methods of methyl mercaptan mainly include adsorption, chemical absorption, biological method and catalytic decomposition. Among them, catalytic decomposition is popular because of its high conversion efficiency, low cost and ability to convert polluting methyl mercaptan into valuable chemical products (such as CH 4 , CO, etc.) and is considered the most suitable method. In recent years, cerium-based catalysts, noble metal catalysts, molecular sieves and their modified catalysts are often used for the catalytic decomposition of methyl mercaptan.

[0004] Although existing catalysts have shown certain effects in the catalytic decomposition of methyl mercaptan, they still face the following problems: 1) High ozone consumption. During the catalytic decomposition process, high ozone consumption not only increases operating costs, but may also lead to the formation of by-products, affecting the purity and quality of the final product. 2) Large catalyst dosage. In order to achieve the ideal catalytic effect, the dosage of existing catalysts is often large, which not only increases the processing cost, but may also make the recovery and reuse of the catalyst difficult, further increasing the environmental burden. 3) Cost issues. Although the catalytic efficiency of precious metal catalysts is high, their cost is high, and the difficulty of recovering precious metals will increase environmental safety costs. 4) Carbon deposition and deactivation.

[0005] Therefore, developing a new catalyst with simple preparation method, higher activity, lower energy consumption, low ozone consumption and low catalyst dosage is a key issue to be solved in the current field of methyl mercaptan tail gas treatment. This will help improve the removal efficiency of methyl mercaptan, reduce treatment costs, and promote the development of environmental protection technology. Summary of the invention

[0006] The present invention provides a nitrogen-doped manganese-loaded layered double hydroxide and its preparation and application. The nitrogen-doped manganese-loaded layered double hydroxide can be used as a catalyst for treating methyl mercaptan. During the application process, the nitrogen-doped manganese-loaded layered double hydroxide exhibits high activity and 3 / CH 3 The SH molar ratio is only 0.8 to achieve a 95% methyl mercaptan conversion efficiency, and the amount of nitrogen-doped manganese-loaded layered double hydroxide is only 0.1 g / L. In addition, after continuous use for 4 hours, the methyl mercaptan conversion efficiency of nitrogen-doped manganese-loaded layered double hydroxide can still be maintained above 90%, proving that the performance attenuation of nitrogen-doped manganese-loaded layered double hydroxide is small and the stability is high.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The invention provides a preparation method of a nitrogen-doped manganese-loaded layered double hydroxide, comprising: ultrasonically mixing a layered double hydroxide and a manganese salt in water to obtain a mixed solution, then adding melamine and water to the mixed solution and ultrasonically mixing again to obtain a precursor, and calcining the precursor to obtain the nitrogen-doped manganese-loaded layered double hydroxide.

[0009] This application utilizes the hydrophilic properties of layered double hydroxides and first mixes them with manganese salts in an aqueous solution; in this process, the manganese salt solution will be wrapped in the layered structure of the layered double hydroxide. Then melamine is added. At this time, because the manganese salt solution is wrapped in the layered structure, melamine cannot directly contact the manganese salt. Finally, during the calcination process, melamine is converted into ammonia at high temperature and enters the layered structure, completing nitrogen doping and manganese loading.

[0010] The order of adding raw materials in this application plays an important role in the structure of the nitrogen-doped manganese-loaded layered double hydroxide finally synthesized. When melamine is added first and then manganese salt is added, the early isolation effect of melamine and manganese salt cannot be achieved, which will lead to a decrease in the utilization rate of manganese salt and nitrogen element, and the proportion of active sites (manganese sites and nitrogen sites) in the composite material synthesized is too small, which makes the catalytic activity of the composite material decrease. More importantly, manganese metal ions cannot be fixed on the layered double hydroxide, and stable catalytic degradation cannot be achieved.

[0011] The sustained-release synthesis method proposed in the present application can help free manganese ions to be effectively anchored on the layered double hydroxide, and after anchoring, they are evenly dispersed in the layered structure and surface of the layered double hydroxide; at the same time, the layered structure of the layered double hydroxide can play a role in fixing the active sites, and the problem of a significant decrease in catalytic conversion efficiency due to separation of active metals will not occur during long-term use.

[0012] Preferably, the solid-liquid ratio in the mixed solution is (0.5-0.7) g:1 mL.

[0013] Preferably, the mass ratio between the manganese in the manganese salt and the layered double hydroxide is (5-10):100.

[0014] Preferably, the molar ratio between the manganese in the manganese salt and the melamine is (0.4-1):4.

[0015] Preferably, the manganese salt is manganese nitrate.

[0016] Preferably, the calcination temperature is 500-600° C., the calcination heating rate is 10-15° C. / min, and the calcination time is 0.5-2 h.

[0017] The present invention also provides a nitrogen-doped manganese-loaded layered double hydroxide prepared by the above preparation method. Based on the weight of the nitrogen-doped manganese-loaded layered double hydroxide, the nitrogen doping amount is a-b wt%, and the manganese loading amount is 5-10 wt%.

[0018] The present invention also provides the nitrogen-doped manganese-loaded layered double hydroxide prepared by the preparation method or the use of the nitrogen-doped manganese-loaded layered double hydroxide in treating methyl mercaptan in flue gas / waste gas by ozone catalytic oxidation at room temperature.

[0019] The mechanism of nitrogen-doped manganese-loaded layered double hydroxide catalyzing the oxidation of methyl mercaptan by ozone is as follows: first, ozone molecules (O 3 ) is adsorbed and activated on the surface of nitrogen-doped manganese-loaded layered double hydroxide. Nitrogen and manganese provide abundant active sites, which can effectively adsorb and activate ozone. Subsequently, ozone molecules are decomposed into active oxygen species (such as ·O 2 - or ·O) as the main oxidant. Subsequently, methyl mercaptan (CH 3 The sulfur atom in the SH) molecule is adsorbed on the surface of the nitrogen-doped manganese-loaded layered double hydroxide, and the manganese center provides an adsorption site to position the methyl mercaptan molecule. The active oxygen species react with the adsorbed methyl mercaptan, resulting in the oxidation of methyl mercaptan. The initial oxidation product is the methyl mercaptan free radical (CH 3 S - ), the further oxidation product is methylthioperoxide (CH 3 SO 2 - ), which is finally oxidized to form sulfur dioxide (SO 2 ) and other by-products. The products generated during the oxidation process can be desorbed from the surface of the nitrogen-doped manganese-loaded layered double hydroxide, so that the surface of the nitrogen-doped manganese-loaded layered double hydroxide can be regenerated and continue to adsorb and activate new ozone and methyl mercaptan molecules, thereby achieving continuous reaction.

[0020] Preferably, in the ozone catalytic oxidation treatment, the molar ratio of ozone to methyl mercaptan in flue gas / waste gas is (0.6-0.8):1.

[0021] Preferably, in the ozone catalytic oxidation treatment, the amount of nitrogen-doped manganese-loaded layered double hydroxide used is 0.05-0.3 g / L.

[0022] When the amount of nitrogen-doped manganese-loaded layered double hydroxide is 0.2 g / L, the conversion of methyl mercaptan is close to 100%, and the conversion efficiency increases with the increase of the amount; however, considering the actual use and economic issues, setting 0.05 to 0.3 g / L can basically meet the use requirements, and the amount exceeding 0.3 g / L can also achieve a considerable effect, but it is not selected for cost considerations. Therefore, the actual amount range in this application should be regarded as greater than 0.05 g / L.

[0023] Preferably, after the nitrogen-doped manganese-loaded layered double hydroxide is used continuously for 4 hours, the conversion rate of methyl mercaptan in flue gas / waste gas is above 90%.

[0024] Therefore, the present invention has the following beneficial effects:

[0025] (1) The present invention provides a nitrogen-doped manganese-loaded layered double hydroxide having nitrogen and manganese dual active sites and having a good ozone catalytic oxidation treatment effect on methyl mercaptan.

[0026] (2) The present invention provides a method for preparing a nitrogen-doped manganese-loaded layered double hydroxide, which utilizes a slow-release synthesis method, has a high utilization rate of manganese ions and can fix manganese metal sites. This characteristic can help the efficient and stable use of nitrogen-doped manganese-loaded layered double hydroxide.

[0027] (3) The nitrogen-doped manganese-loaded layered double hydroxide provided by the present invention is 3 / CH 3 When the SH molar ratio is 0.8, the conversion efficiency of methyl mercaptan can reach 95%, and the dosage of nitrogen-doped manganese-loaded layered double hydroxide is as low as 0.1 g / L.

[0028] (4) After the nitrogen-doped manganese-loaded layered double hydroxide provided by the present invention is used continuously for 4 hours, the conversion efficiency of the nitrogen-doped manganese-loaded layered double hydroxide to methyl mercaptan can still be maintained at more than 90%, which proves that the performance attenuation of the nitrogen-doped manganese-loaded layered double hydroxide is small and the stability is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a graph showing the methyl mercaptan conversion capacity of each catalytic material under liquid phase conditions;

[0030] Figure 2 is a graph showing the methyl mercaptan conversion capacity of each catalytic material under gas phase conditions;

[0031] Figure 3 The effect diagram of nitrogen-doped layered double hydroxides of iron-loaded and manganese-loaded catalysts;

[0032] Figure 4 is a graph showing the methyl mercaptan conversion capabilities of different catalytic materials;

[0033] Figure 5 The methyl mercaptan conversion capacity diagram of Mn LDH-M at different catalyst dosages;

[0034] Figure 6 is the methyl mercaptan conversion capacity diagram of Mn LDH-M under different ozone concentrations;

[0035] Figure 7 The methyl mercaptan conversion capacity of Mn LDH-M under different liquid environments;

[0036] Figure 8 is the methyl mercaptan conversion capacity diagram of Mn LDH-M at different methyl mercaptan concentrations;

[0037] Fig. 9 This is the stability test result of Mn LDH-M. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0039] [Example]

[0040] Manganese nitrate tetrahydrate, melamine and ferric nitrate in this part were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Layered hydroxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; LDH for short, general formula: [M(II) 1-x M(III) x (OH) 2 ] x +(An - ) x / n ·mH 2 O, where M(II) represents a divalent metal cation (such as Mg 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ etc.), M(III) represents a trivalent metal cation (such as Al 3+ , Fe3+ Cr 3+ etc.), - For interlayer exchangeable anions (such as CO 3 2- 、NO 3 - , Cl - etc.), x is the molar fraction of M(III) in the total metal ions (usually ranging from 0.2 to 0.33), and m is the number of interlayer water molecules. Montmorillonite was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., montmorillonite k-10, referred to as MMT.

[0041] Example 1

[0042] 0.5g layered hydroxide (6.6mmol) and 0.173g manganese nitrate tetrahydrate (0.7mmol) were mixed in 1mL deionized water, shaken evenly, and ultrasonicated for 20min. Then 0.5g melamine (4mmol) and 1mL deionized water were added, stirred evenly, and ultrasonicated for 10min. The temperature was raised from room temperature to 550℃ at a heating rate of 13℃ / min and maintained for 1h to obtain nitrogen-doped manganese-loaded layered double hydroxide, in which the nitrogen doping amount was 3-4wt% and the manganese loading amount was 7.5wt%, recorded as Mn LDH-M (Note: the nitrogen doping amount cannot be accurately measured due to equipment problems, so it is written as a range value).

[0043] Comparative Example 1

[0044] 0.5g layered hydroxide (6.6mmol) and 0.5g melamine (4mmol) and 1mL deionized water were stirred evenly and ultrasonicated for 20min. Then 0.173g manganese nitrate tetrahydrate (0.7mmol) and 1mL deionized water were added, stirred evenly and ultrasonicated for 10min. The temperature was raised from room temperature to 550℃ at a heating rate of 13℃ / min and maintained for 1h to obtain nitrogen-doped manganese-loaded layered double hydroxide, recorded as Mn-M / LDH.

[0045] Comparative Example 2

[0046] This comparative example is substantially the same as Example 1, except that the layered hydroxide is replaced by an equal mass of montmorillonite, 0.5 g of montmorillonite (2 mmol), recorded as Mn MMT-M.

[0047] Comparative Example 3

[0048] This comparative example is substantially the same as Example 1, except that manganese nitrate tetrahydrate is replaced by an equal molar amount of ferric nitrate nonahydrate, 0.283 g ferric nitrate nonahydrate (0.7 mmol), recorded as Fe LDH-M.

[0049] Comparative Example 4

[0050] This comparative example is basically the same as Example 1, except that the addition of manganese nitrate tetrahydrate is omitted, and is recorded as LDH-M.

[0051] Comparative Example 5

[0052] This comparative example is substantially the same as Example 1, except that the addition of layered double hydroxide is omitted and recorded as Mn-M.

[0053]

Performance test

[0054] 1. Methyl mercaptan conversion capacity of different catalyst supports

[0055] 70 mg of each Mn MMT-M and montmorillonite (MMT), 35 mg of each Mn LDH-M and layered hydroxide (LDH) were tested under liquid phase conditions. 70 mg of each Mn MMT-M, montmorillonite (MMT), Mn LDH-M and layered hydroxide (LDH) were tested under gas phase conditions.

[0056] The performance of the above catalysts in catalytic oxidation of methyl mercaptan by ozone was explored. Gas phase experimental parameters 1: 180 ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 : 5mL / min. Gas phase experimental parameter 2: 240ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 :5mL / min. Liquid phase experimental parameters 1: 180ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, 350mL water. Liquid phase experimental parameters 2: 240ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, 350mL of water.

[0057] After the reaction was completed, liquid / gas chromatography was used to detect the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan. The test results are shown in Figures 1-2 .

[0058] Figure 1 The results show that the performance of MMT declines after nitrogen doping and manganese loading, while the performance of LDH is effectively improved after nitrogen doping and manganese loading. In theory, both MMT and LDH have layered structures and similar physical and chemical properties. In theory, the performance after doping and loading should be similar. However, through experiments conducted by the applicant, it was found that although the performance of the two is similar, the results shown are completely different. It is speculated that this may be because the interlayer spacing of the layered double hydroxide is large, and the interlayer contains exchangeable anions and water molecules; after nitrogen doping and manganese loading, these anions and water molecules can effectively regulate the interlayer environment, so that the manganese ions are evenly distributed and maintain a high catalytic activity. The interlayer spacing of montmorillonite is small, and the interlayer mainly contains water molecules and a small amount of exchangeable cations; nitrogen doping and manganese loading may cause crowding of the interlayer space, affecting the free movement of interlayer ions, thereby reducing its catalytic activity.

[0059] In this study, the applicant first conducted exploratory experiments in the liquid phase at a catalyst dosage of 70 mg to evaluate the catalytic activity of Mn LDH-M and LDH. The experimental results showed that both substances showed good reactivity at this dosage. Based on these preliminary results, the applicant further optimized the catalyst dosage of Mn LDH-M and LDH in the liquid phase and found that reducing the catalyst dosage to 35 mg could still maintain a high reactivity.

[0060] 2. Differences in methyl mercaptan conversion ability caused by different active metal centers

[0061] 35 mg of each Mn LDH-M and Fe LDH-M were tested under liquid phase conditions to explore the performance of the above catalysts in catalyzing the catalytic oxidation of methyl mercaptan by ozone. Liquid phase experimental parameters: 240 ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, 350mL of water.

[0062] After the reaction was completed, liquid chromatography was used to detect the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan. The test results are shown in Figure 3 .

[0063] observe Figure 3It can be seen that the conversion capacity of methyl mercaptan of Fe LDH-M with Fe as the active metal center is significantly lower than that of Mn LDH-M with Mn as the active metal center under the same reaction conditions. This shows that Mn has better performance in the catalytic oxidation of methyl mercaptan as an active metal center. It may be due to the electronic structure and chemical properties of Mn that it can more effectively activate ozone molecules and promote the reaction between methyl mercaptan molecules and active oxygen species when it cooperates with nitrogen-doped loaded layered double hydroxides. Further studies have found that the effect of different active metal centers on catalytic performance may be related to their ability to regulate the generation and stability of active oxygen species. Mn may be more conducive to the generation of highly active oxygen species and can maintain the appropriate stability of these active oxygen species on the catalyst surface, thereby enhancing the oxidation capacity of methyl mercaptan. Fe is relatively weak in this regard, resulting in its low efficiency in catalyzing the conversion of methyl mercaptan. This result provides an important reference for further optimizing the design of catalysts, that is, the selection of a suitable active metal center is crucial to improving the catalytic oxidation performance of nitrogen-doped loaded layered double hydroxides for methyl mercaptan. Subsequent research can further explore the synergistic mechanism between Mn and other elements, as well as how to further optimize the loading and distribution of Mn to achieve higher catalytic activity and selectivity. At the same time, it is also possible to consider combining Mn with other materials with specific functions to develop a methyl mercaptan treatment catalyst with better performance, providing a more effective technical means to solve the problem of methyl mercaptan waste gas pollution.

[0064] 3. Synergistic effects of nitrogen and manganese active sites

[0065] 35 mg of each Mn LDH-M, Mn-M, LDH-M, Mn-M / LDH and layered hydroxide (LDH) were tested under liquid phase conditions. The performance of the above catalysts in catalyzing the catalytic oxidation of methyl mercaptan by ozone was explored. Liquid phase experimental parameters 1: 180 ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, 350mL water. Liquid phase experimental parameters 2: 210ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, 350mL water. Liquid phase experimental parameters 3: 240ppm O 3 ; 300ppm CH3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, 350mL of water.

[0066] After the reaction was completed, liquid chromatography was used to detect the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan. The test results are shown in Figure 4 .

[0067] observe Figure 4 It can be seen that the ability of LDH-M materials to catalyze methyl mercaptan is greatly reduced after losing the manganese site, which proves that there is a synergistic effect between the manganese site and the nitrogen site, and the manganese site itself has an effect on the catalysis of methyl mercaptan. In addition, the ability of the Mn-M / LDH material to catalyze methyl mercaptan is also affected by changing the addition order.

[0068] 4. Performance test of Mn LDH-M

[0069] ① Catalyst dosage

[0070] The performance of the above catalyst in catalyzing ozone oxidation of methyl mercaptan was explored.

[0071] Liquid phase experimental parameters 1: 180ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH30mL / min, O 3 5mL / min, 350mL of water, the amount of catalyst was controlled to 0.175g, 0.35g, and 0.70g respectively.

[0072] Liquid phase experimental parameters 2: 240ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH30mL / min, O 3 5mL / min, 350mL of water, the amount of catalyst was controlled to 0.175g, 0.35g, and 0.70g respectively.

[0073] After the reaction was completed, liquid chromatography was used to detect the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan. The test results are shown in Figure 5 .

[0074] observe Figure 5It can be seen that with the increase of catalyst dosage, the catalytic efficiency of methyl mercaptan is improved. When the catalyst dosage is 0.1 g / L, the conversion rate reaches more than 95%.

[0075] ②Ozone concentration

[0076] The performance of the above catalyst in catalytic ozone oxidation of methyl mercaptan was explored. Liquid phase experimental parameters: catalyst dosage 35 mg; 300 ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, water 350mL, ozone concentration 90ppm, 180ppm, 240ppm, 270ppm, 360ppm. After the completion of the process, liquid chromatography was used to test the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan. The test results are shown in Figure 6 .

[0077] observe Figure 6 It can be seen that with the increase of ozone concentration, the catalytic efficiency of methyl mercaptan is improved. When the ozone concentration is 240ppm, the conversion rate reaches more than 95%. 3 / CH 3 The SH molar ratio is 0.8.

[0078] ③Liquid environment

[0079] The performance of the above catalyst in catalyzing the catalytic oxidation of methyl mercaptan by ozone was explored. Liquid phase experimental parameters: catalyst dosage 35 mg; 240 ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, the water environment was controlled to be ultrapure water and tap water. After the reaction was completed, the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan was tested by liquid chromatography. The test results are shown in Figure 7 .

[0080] observe Figure 7 It can be seen that the application effects of the Mn LDH-M prepared in the present application in tap water and ultrapure water are very ideal, and the methyl mercaptan conversion rate is maintained at more than 95%.

[0081] ④ Methyl mercaptan concentration

[0082] The performance of the above catalyst in catalyzing the catalytic oxidation of methyl mercaptan by ozone was explored. Liquid phase experimental parameters: catalyst dosage 35 mg; 240 ppm O 3 ; Room temperature; Gas flow rate: N 265mL / min, O 3 5mL / min, 350mL of water, and the concentration of methyl mercaptan was controlled to be 100ppm, 300ppm, and 500ppm respectively. After the reaction was completed, liquid chromatography was used to detect the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan. The test results are shown in Figure 8 .

[0083] observe Figure 8 It can be seen that with the increase of methyl mercaptan concentration, the catalytic efficiency of methyl mercaptan decreases, but its conversion rate remains above 90%.

[0084] ⑤Stability

[0085] The performance of the above catalyst in catalyzing the catalytic oxidation of methyl mercaptan by ozone was explored. Liquid phase experimental parameters: catalyst dosage 35 mg; 240 ppm O 3 ; 300ppm CH 3 SH; room temperature; gas flow rate: N 2 65mL / min, CH 3 SH 30mL / min, O 3 5mL / min, 350mL of water.

[0086] After the reaction was completed, liquid chromatography was used to detect the conversion rate of methyl mercaptan in the process of ozone catalytic oxidation of methyl mercaptan. The test results are shown in Fig. 9 .

[0087] observe Fig. 9 It can be seen that after continuous use for 4 hours, the conversion efficiency of Mn LDH-M for methyl mercaptan can still be maintained above 90%, proving that the performance attenuation of nitrogen-doped manganese layered double hydroxide is small and the stability is high.

Claims

1. A method for preparing a nitrogen-doped manganese-loaded layered double hydroxide, characterized in that: include: The layered double hydroxide and manganese salt are ultrasonically mixed in water to obtain a mixed solution, melamine and water are then added to the mixed solution and ultrasonically mixed again to obtain a precursor, and the precursor is calcined to obtain nitrogen-doped manganese-loaded layered double hydroxide.

2. The preparation method according to claim 1, characterized in that The solid-liquid ratio in the mixed solution is (0.5-0.7) g:1 mL.

3. The preparation method according to claim 1, characterized in that: The mass ratio between the manganese in the manganese salt and the layered double hydroxide is (5-10):

100.

4. The preparation method according to claim 1, characterized in that: The molar ratio between the manganese in the manganese salt and the melamine is (0.4-1):

4.

5. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-600° C., the calcination heating rate is 10-15° C. / min, and the calcination time is 0.5-2h.

6. The nitrogen-doped manganese-loaded layered double hydroxide prepared by the preparation method according to any one of claims 1 to 5, characterized in that: Based on the weight of the nitrogen-doped and loaded manganese layered double hydroxide, the nitrogen doping amount is 1-10wt%, and the manganese loading amount is 5-10wt%.

7. Use of the nitrogen-doped manganese-loaded layered double hydroxide prepared by the preparation method according to any one of claims 1 to 5 or the nitrogen-doped manganese-loaded layered double hydroxide according to claim 6 in treating methyl mercaptan in flue gas / waste gas by ozone catalytic oxidation at room temperature.

8. The use according to claim 7, characterized in that In the ozone catalytic oxidation treatment, the molar ratio of ozone to methyl mercaptan in flue gas / waste gas is (0.6-0.8):

1.

9. The use according to claim 7, characterized in that In the ozone catalytic oxidation treatment, the amount of nitrogen-doped manganese-loaded layered double hydroxide used is 0.05-0.3 g / L.

10. The use according to claim 7, characterized in that After the nitrogen-doped manganese-loaded layered double hydroxide is used continuously for 4 hours, the conversion rate of methyl mercaptan in flue gas / waste gas is above 90%.

Citation Information

Patent Citations

  • Nitrogen doped hydrotalcite adsorbent preparation method

    CN109173978A

  • Nitrogen-doped high-entropy layered hydroxide and preparation method thereof

    CN118854345A

  • Preparation of manganese-doped layered double hydroxide drug-loaded nanoparticles and application of manganese-doped layered double hydroxide drug-loaded nanoparticles in tumor phototherapy and immune combined therapy

    CN118903459A

  • Process for deacidification of a natural gas using layered double hydroxides

    EP2155359A2

  • Air electrode catalyst for metal-air secondary battery

    JP2018067494A